1996
DOI: 10.1172/jci118475
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and type II collagenolytic activity of matrix metalloproteinase-13 from human osteoarthritic cartilage.

Abstract: Proteolysis of triple-helical collagen is an important step in the progression toward irreversible tissue damage in osteoarthritis. Earlier work on the expression of enzymes in cartilage suggested that collagenase-1 (MMP-1) contributes to the process. Degenerate reverse transcription polymerase chain reaction experiments, Northern blot analysis, and direct immunodetection have now provided evidence that collagenase-3 (MMP-13), an enzyme recently cloned from human breast carcinoma, is expressed by chondrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
668
0
9

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 877 publications
(712 citation statements)
references
References 22 publications
25
668
0
9
Order By: Relevance
“…Our results are consistent with the previous finding that MMP-13 production is up-regulated in OA chondrocytes and synovial cells and is thought to play a critical role in cartilage degradation (40)(41)(42)(43). We previously demonstrated that an anti-OPN antibody (M5), which interferes with the binding of OPN to integrin receptors, up-regulated MMP-13 expression in cultured tendon fibroblasts of WT mice (14).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the previous finding that MMP-13 production is up-regulated in OA chondrocytes and synovial cells and is thought to play a critical role in cartilage degradation (40)(41)(42)(43). We previously demonstrated that an anti-OPN antibody (M5), which interferes with the binding of OPN to integrin receptors, up-regulated MMP-13 expression in cultured tendon fibroblasts of WT mice (14).…”
Section: Discussionsupporting
confidence: 93%
“…MMP-13 has a particular affinity for type II collagen and selectively enhances cleavage and denaturation of this type of collagen (43), and can also cleave aggrecan at specific sites (44). Interestingly, recent studies have also shown that retinoid-related signals strongly enhance the induction of MMP-13 in chondrocytic cells through the action of RAR-RXR heterodimers (45).…”
Section: Discussionmentioning
confidence: 99%
“…All 3 known human collagenases, proMMPs 1, 8, and 13, are synthesized by human articular chondrocytes and are up-regulated by proinflammatory cytokines (61)(62)(63)(64)(65). Moreover, we recently demonstrated that the combination of IL-1␣ and OSM was able to synergistically induce messenger RNA (mRNA) expression for all 3 collagenases in chondrocytes, with a concomitant increase in MT1-MMP expression (66).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-13 protein is present in the pannus-hard tissue junction in RA (69) and in osteoarthritic cartilage (68). However, type II collagen is the principal collagen in cartilage and is cleaved most efficiently by MMP-13 (25,63).…”
Section: Discussionmentioning
confidence: 99%